2016
DOI: 10.31729/jnma.2592
|View full text |Cite
|
Sign up to set email alerts
|

An Interesting Case of Basal Cell Carcinoma with Raynaud’s Phenomenon Following Chronic Arsenic Exposure

Abstract: Arsenic is commonly known to be associated with squamous cell carcinoma. Among the lesser known associations is basal cell carcinoma and even rarer is its effect on blood vessels causing peripheral vascular disease. Here we present a case of a 55 yr old man with ulceroproliferative lesions on scalp and forehead along with several hyperpigmented patches on trunk and extremities. He had symptoms suggestive of Raynaud’s phenomenon that eventually led to digital gangrene. FNAC was done which was suggestive of basa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Multiple studies have demonstrated that eliminating arsenic exposure is strongly associated with preventing further cutaneous manifestations 5,41–47 . Although both Tay et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have demonstrated that eliminating arsenic exposure is strongly associated with preventing further cutaneous manifestations 5,41–47 . Although both Tay et al.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have demonstrated that eliminating arsenic exposure is strongly associated with preventing further cutaneous manifestations. 5,[41][42][43][44][45][46][47] Although both Tay et al and Wagner et al's findings suggested dimercaprol may only be effective in acute and subacute arsenic toxicity, other chelation therapy may improve some dermatological presentations in the chronic phase. 15,16 A case report and case series demonstrated a positive association between individuals taking oral Dpenicillamine with improvement of cutaneous presentations such as palmoplantar hyperkeratosis that were suspected to be chronic arsenic-induced.…”
Section: Treatment Of Chronic Arsenic Toxicity Dermatological Present...mentioning
confidence: 99%
“…Immunocompromised patients have also been reported to have a higher risk of developing BCC than the general population [ 9 , 10 ] and BCCs appear to show a more aggressive behavior in these patients [ 11 ]. Chronic exposure to arsenic might also be responsible for the incidence of BCC development [ 12 , 13 , 14 ]. BCCs can be generally classified in four groups according to the form of growth pattern.…”
Section: Introductionmentioning
confidence: 99%